DESIGNING PROJECT-BASED LEARNING IN ESP CLASS - Dian Arsitades Wiranegara (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Project-Based Learning of ESP is developed to involve as well as to encourage students to be active in the process of teaching and learning. Students can fully contribute in the project once they are asked in the inquiry process by giving a guiding question and the teacher guides them into a collaborative project integrated in curriculum. A guiding question here, must be based on the issues and topics addressing the real world problems. This also means that the project learning can help learners experience a meaningful learning, based on constructivism philosophy. Learners are given chance to explore and find any source of information by reading books, then communicate it to others or presenting their ideas. Hence, at the end of teaching and learning process, learners reflect to the project that has been conducted. At this phase, all learners are asked to share their experiences as well as their feeling during the project. Teacher and learners can share and develop it into a discussion in order to improve their performance